The Influence of the Contact Pressure on the Value of the Coefficient of Friction - I. Bijelić; N. Mor; M. Živković; V. Tubin (Tribology in Industry, 2017)
Experimental research was carried out on the tribometer of high reliability of measurement. The paper discusses the impact of normal contact pressure on the value of the coefficient of friction. Elements that are in contact are filled steel rollers with different mass and diameters that slide on the hollow roller shaped like a ring. These contact elements are completely submerged in oil and have identical lubrication requirements. The results of this study indicate the significant influence of the level of normal load and contact pressure on the coefficient of friction.